Aspects of Content and Language in the Malaysian Arbitration Act - Hashim, Azirah (HERMES - Journal of Language and Communication in Business, 2004)
This paper focusses on the Malaysian Arbitration Act of 1952 and examines some aspects of content in the Act as compared to that in the model Law. Some linguistic analysis is carried out and differences in terms of speciﬁcity and lack of adequate speciﬁcation and differences in legal systems and procedures are discussed. The analysis shows that content and language are inﬂuenced by national requirements and concerns, culture, legal system and other constraints.